SEMIOTICAL AND EMPIRICAL TRENDS IN THE SEMIOTIC APPROACH TO THE TRAINING OF PRIMARY GRADE TEACHERS - Abdusamatov Alisher Sobirovich (Bright Mind Publishing, 2025)
This article provides information to junior students of general secondary schools on the semiotic approach, its fields and their boundaries and types, the importance, history and application of semiotic aspects, necessary pedagogical conditions, scientists and their views, branches, directions and applications of semiotics. in our everyday life. It is described how we use it.
Keywords: Semiotics, education, educational system, philosophy, pragmatics, syntax.